The relationship between the extortionist and the victim in a case of extortion: a Conversation Analysis approach - Lazo García, Verónica (2022)
Extortion is a crime where an individual forces another individual to hand over a patrimonial asset by means of intimidation, which is expressed by aggressive actions and also verbally, through negotiation (Goicochea, 2018). The purpose of this article is to describe the power relationship between the extortionist and the victim through the study of conversation. To do so, five telephone conversations from a case of extortion were analyzed. We employed the theoretical-methodological framework of conversation analysis (proposed by Val.Es.Co Group, 2014), politeness (Brown and Levinson, 1987) and discourtesy (Kaul de Marlangeon, 2017). The results show that the conversations are formally characterised by the use of the periphrasis ir +a +infinitive; of conditional and imperative constructions; and of filler, contact and counterargumentative discourse markers. Also, the extortioner's power is evident in his control by cutting off calls and initiating all adjacent pairs; however, he does not have absolute power over the victim, as the victim resists, gives suggestions and complains. In this type of interaction, such actions constitute politeness and discourtesy strategies deployed by both interlocutors.